Development of emotion expressive humanoid head - Mohd Farid Bin Md Alias (Kulliyyah of Engineering, International Islamic University Malaysia, 2012)
Advances in robotics technology have paved way to the innovation of sophisticated robots with improved capacity and capability to perform tasks such as humanoids. As humanoids are gradually adapted within human-existing environment, interactions with humans are inevitable and thus there is a need to develop human-friendly humanoids particularly with expressive face to portray emotions. These robots, known as humanoid heads, can be of anthropomorphic (human-like) or iconic (cartoonish) look. Iconic humanoid heads are generally less prone to anthropomorphism pitfalls of Mori's Uncanny Valley theory. However, in terms of facial elements, some iconic humanoid head designs tend to exclude the mouth cues even though the mouth region can be effective in conveying emotional displays. In this thesis, a new humanoid head design with unique mouth mechanism is presented. The humanoid head, named as AMIR-III is designed and developed based on AMIR Model of Facial Expression (AMEr). AMIR-III possesses 18 DOFs in total and two eyes with built-in cameras. Together with other facial cues, its 3-DOF mouth forms the basic facial expressions of AMIR-III namely happy, sad, angry and surprised. From an expression recognition survey, the recognition rates of AMIR-III facial expressions are found to be generally recognizable to human beings and at par with recognition rates of other humanoid heads in comparison with slight variation on its happy expression.